Investigating the gut and blood microbiome in Parkinson’s disease, schizophrenia, and posttraumatic stress disorder - Rust, Catharina Magdalena (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.